The Effect of Gymnastics on the Quality of Life of the Elderly at the Social Rehabilitation Center for the Elderly in North Maluku Province (International Journal of Scientific Research and Management (IJSRM), 2022)
Old age or old age is not a disease, but this condition can cause social problems. At the time of entering old age, body functions can no longer function properly, so the elderly need a lot of help in carrying out their life activities. Not to mention the various diseases that accompany the condition of the elderly that make them need extra attention from the people around them. Sports activities will help the body stay fit and fresh because it trains bones to stay strong, encourages the heart to work optimally, and helps eliminate free radicals that roam the body, in other words, have good physical fitness if the heart and blood circulation are good so that the whole body can run. Its function for a long time. Elderly exercise is a series of tone movements that are regular, directed and planned in the form of physical exercise that affects the physical exercise of the elderly. The purpose of this study was to determine the effect of elderly exercise on the quality of life of the elderly at the Social Institution for the Social Rehabilitation of the Elderly in North Maluku Province. Pre-experimental research design. The design used in this study is a one group pretest-posttest design with control group. In the independent statistical test the sample T test at the time after the intervention was given, it showed that the p-value (0.000) <0.05, which means that there is a difference in the average quality of life of the elderly between those who do exercise accompanied by an instructor and those who are not accompanied by an instructor. There is an effect of elderly exercise on the quality of life of the elderly.